Novel exact wave solutions of the (4+1)-dimensional Boiti-Leon-Manna-Pempinelli model via application of three mathematical methods - Seadway, Aly R.; Ali, Asghar; Bekir, Ahmet; Cevikel, Adem C.; Guener, Oezkan (SPRINGER, 2024)
In this manuscript, novel exact results to the hyperbolic local (4+1)-dimensional BLMP model are established with the applications of three mathematical methods. The concern model is used to signify the wave propagation over an incompressible fluid. The resulting solutions are also endorsed by the use of computational software like Mathematica 13. The vigorous structures of selected acquired solutions are portrayed in 2-dimensional and 3-dimensional graphs by imparting different selection of parameters. Hence the outcomes proved that our proposed methods are straightforward and efficient tools to construct travelling wave solutions of many nonlinear problems in physics and engineering.
Keywords: (4+1)-dimensional BLMP equation; Mathematical methods; Exact solutions; SOLITON-SOLUTIONS; SCHRODINGER-EQUATION; ABUNDANT; Engineering; Physics; Optics